Design, modeling and simulation of an anchorless nano-electro- mechanical nonvolatile memory - Vaddi, Ramesh (2013)
Non Volatile Memories (NVMs) based on a storage layer, like FLASH, suffer from poor retention at high temperature, high voltage writing, and wear out while cycling. This paper presents the structure, operation and modeling details of a new NVM based on nano-electromechanical memory (NEM) cell having two stable mechanical positions and actuated by electrostatic forces. Permanent retention is obtained by adhesion forces only, eliminating the leakage observed in all types of storage layers. First part of the work focus on the introduction of single cell of NEM based NVM structure and operation. The second part of the work focus on NEM based NVM modeling and behavior implementation with Verilog-A compact modeling and testing in Cadence environment. The results verify the correct functionality and scalability of the new NEM cell. With the anchorless shuttle, the design is highly eased and scalable, compared to standard anchor based NEM structures.